Analysis of the Power of Common Diagnostic Tools in the Management of Acute Pancreatitis - Markus Nistal; Malai Zoltani; Ansgar W. Lohse; Nicola Di Daniele; Manfredi Tesauro; Andrea Pace (Gastroenterology Research and Practice)
Acute pancreatitis (AP) is a serious medical condition usually associated with severe upper abdominal pain. The purpose of our study is to assess the therapeutic consequences of contrast-enhanced computed tomography (CE-CT) and the predictive value of CRP for severe pancreatitis. We included patients with a threefold increase of plasma lipase who had received a CE-CT or had a CRP of =150 mg/dl. A total of 74 out of 283 patients got a contrast-enhanced CT scan; in 11 cases the CT was followed by endoscopic or surgical interventions as therapeutic consequences compared with 19 out of 50 control cases. 69 out of 283 patients (24,3%) had CRP >150 mg/dl within 48 hours after admission. 32 of them had SAP. The CRP cutoff of 150 mg/L had a sensitivity of 80% and a specificity of 65%. The positive predictive value for SAP in patients beyond the cutoff is 46.4%. The negative predictive value for SAP in patients below the cutoff was 89.5%. Our results support the opinion that an early CE-CT is usually not indicated. CRP helps to assess the course of AP; levels below 150 mg/dl between the first 48 h indicate a mild course in most of the cases.